2010
DOI: 10.1007/s11270-010-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace Analysis of N-Nitrosamines in Water Using Solid-Phase Microextraction Coupled with Gas Chromatograph–Tandem Mass Spectrometry

Abstract: A method that utilizes solid-phase microextraction (SPME) coupled with gas chromatography (GC) and chemical ionization tandem mass spectrometry (MS/MS) was developed for analyzing a group of emerging pollutants, N-nitrosamines, in water. The developed analytical method requires a water sample of less than 5 ml and only 1.5 h for complete analysis. The method detection limits for N-nitrosodimethylamine (NDMA), N-nitrosodiethylamine, and N-nitrosodin-propylamine were in the range of 3.2 to 3.5 ng/l; for N-nitros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The highest nitrosamine levels (mainly NDMA, NDEA and NMor residues) were detected in samples after ozonation and high chlorination processes. A SPME-GC-MS/MS based methodology has been recently reported [19], allowing the fast and selective determination of four N-nitrosamines in water. Only NDMA was detected in most of the water treatment plant (WTP) samples investigated and below 9 ng L −1 in tap waters.…”
Section: Introductionmentioning
confidence: 99%
“…The highest nitrosamine levels (mainly NDMA, NDEA and NMor residues) were detected in samples after ozonation and high chlorination processes. A SPME-GC-MS/MS based methodology has been recently reported [19], allowing the fast and selective determination of four N-nitrosamines in water. Only NDMA was detected in most of the water treatment plant (WTP) samples investigated and below 9 ng L −1 in tap waters.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples include Hung et al [20] and Llop et al [21]. The most common alternative to this has been analysis by high pressure liquid chromatography with tandem mass spectrometry (HPLC-MS/MS) [22][23][24].…”
mentioning
confidence: 99%
“…18 Kadmi et al (2014) and Kadmi et al (2015c). In their work, Hung et al (2010) also reported that the complicated natural water matrix did not affect the performance of the SPME-GC/MS/MS method developed for the trace analysis of N-nitrosamines. At contrary, the matrix effect appears as significant in the case of the analysis of NDMA in wastewater samples because of the high organic matter concentrations.…”
Section: Matrix Effectmentioning
confidence: 99%
“…(Perez et al, 2008;Huang et al, 2010;Taguchi et al, 1994). However, the LLE generally requires large amounts of organic solvents, potentially harmful for environment, and the analytical process is time consuming and labor-intensive (Hung et al, 2010). Indeed the time required for analyte extraction and quantification with such technique may range from 3 to 16 h.…”
Section: 2 Optimization Of Separation Conditionsmentioning
confidence: 99%